2020
DOI: 10.1038/s41419-020-02914-y
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stromal cells promote corneal wound healing by accelerating the clearance of neutrophils in cornea

Abstract: The dome-shaped cornea is a transparent, non-vascularized, and epithelialized highly organized tissue. Physical and chemical injuries may trigger corneal wound healing (CWH) response and result in neovascularization that impairs the visual function. CWH involves not only migration, proliferation, and differentiation of the cells in different layers of cornea, but also the mobilization of immune cells. We demonstrated here that human adipose-derived mesenchymal stromal cells (ADSCs) could effectively inhibit ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The core mechanism in this process is paracrine rather than MSCs proliferation and differentiation. Exosomes have been the most studied paracrine substance during the past few years and are widely used as a treatment strategy for inflammatory diseases, such as neuropathic pain [ 22 ], spinal cord injury [ 35 ], and Parkinson’s disease [ 53 ]. A few unique advantages make it possible for MSC-derived exosomes to replace MSCs in central nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The core mechanism in this process is paracrine rather than MSCs proliferation and differentiation. Exosomes have been the most studied paracrine substance during the past few years and are widely used as a treatment strategy for inflammatory diseases, such as neuropathic pain [ 22 ], spinal cord injury [ 35 ], and Parkinson’s disease [ 53 ]. A few unique advantages make it possible for MSC-derived exosomes to replace MSCs in central nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We found that human MSC(AD)s could effectively inhibit neovascularization and reduce the opacification of ethanol-injured cornea via promoting the clearance of neutrophils during the granulation stage. 128 Likewise, another study demonstrated that MSCs extracted from corneas and then embedded in fibrin gel for local application prevented corneal neovascularization after corneal injury in mice. These effects were significantly abrogated by knocking down the pigment epithelium-derived factor (PEDF) expression in cornea-derived MSCs (MSC(C)s).…”
Section: Major Factors Released By Mscsmentioning
confidence: 99%
“…Similarly, amniotic membrane MSCs decrease NET release as well as the production of reactive oxygen species through producing TNF-stimulated gene 6 ACCEPTED MANUSCRIPT / CLEAN COPY 13 protein (TSG-6) [35]. Few data are available on the inhibition of neutrophil activity by ASCs but their clinical efficacy in cornea repair was attributed to their capacity to trigger neutrophil clearance in a preclinical mouse model [36]. In our study, the use of frozen AT-SVF precluded any analysis of neutrophil infiltration and activation in situ.…”
Section: Discussionmentioning
confidence: 99%